Faktor Demografi Dan Literasi Finansial Terhadap Minat Masyarakat Menabung Di Bank Syariah (Studi Kasus Pada Masyarakat Kecamatan Air Salek Kabupaten Banyuasin) - Sela Puji Lestari; Fakhrina; Iceu Sri Gustiana (CV. ITTC INDONESIA, 2024)
The aim of this researcher is to find out whether there is an influence of demographics and financial literacy on people’s interest in saving in Islamic banks (case study of the people of Air Salek sub-district, Banyuasin regency). Data analysis in this research used Smart-PLS 3.0 with correlation research methods. The data used is primary data. Data collection was by distributing questionnaires to 100 people in the Air Salek District, Banyuasin Regency. The results show that the results of the first hypothesis test show that the relationship between demographic variables and people's interest in saving has a correlation value of 0.643. This value means that there is a positive influence between demographic variables and people's interest in saving in Air Salek District, Banyuasi Regency. The results of the second hypothesis test show that there is a relationship between the financial literacy variable and interest people's savings have a correlation value of 0.554. This value means that there is a positive influence between the financial literacy variable and people's interest in saving in Air Salek District, Banyuasin Regency. Based on the calculation results, it shows that demographic variables and financial literacy variables have a positive effect on people's interest in saving in Air Salek District. This is proven by the R-square value of 0.458. This shows that the greater the influence of demographic variables and financial literacy, the better people's interest in saving will be.